Analysis of WiMAX Positioning Using Received- Signal-Strength Method - Awang Md Isa, Azmi; Mohamad Isa, Mohd Sa'ari; Mohd Zin, Mohd Shahril Izuan; Haron, Nor Zaidi; Ja'afar, Abd Shukur (Penerbit Universiti, UTeM, 2013)
This paper presents an analysis of WiMAX positioning by using received-signal-strength (RSS) method. A simulator was developed using MATLAB to demonstrate the ability of RSS method for WiMAX positioning. With this simulator, the user can specify their own data or parameters in analyzing and obtaining the target object location. In this study, the analysis was done in three different scenarios that simulate various conditions for WiMAX positioning. Result shows that channel or propagation models are crucial part in the process of analyzing the communication system where it will affect the performance of positioning detection. Selection of perfect model that resemble the real environment will led to better wireless positioning system. By the performance evaluation, the user can plan better simulation system and can create more accurate algorithms for radio positioning.